Faktor Perilaku yang Berhubungan dengan Hasil Pemeriksaan Jentik Pasca Keberadaan Surveilans Angka Bebas Jentik di Kecamatan Tembalang Kota Semarang - Diana Andriyani Pratamawati; Widiarti Widiarti; Wiwik Trapsilowati; Riyani Setiyaningsih (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Tembalang Subdistrict is still ranked as the first highest IR Dengue in Semarang City in 2014-2016. Incidence rate of dengue in Tembalang Sub District in 2016 was Dengue hemorrhagic fever (DHF) IR 166.89/100,000 population with Case Fatality Rate (CFR) 1.02%. The Semarang City Government has implemented PERDA No.5 of 2010 concerning DHF control with the establishment of special larvae monitoring officers namely Semantik (Semarang Bebas Jentik) and Gasurkes (Health Surveillance Officer) to conduct routine larval monitoring and socialize PSN-3M Plus. However, dengue cases in Tembalang District continue to exist.The purpose of the study was to identify behavioral factors related to monitoring larva presence in Tembalang District, Semarang City. This study is based on the cross sectional method, with quota sampling was used to recruit 100 respondents. The criteria for the case were the latest DHF cases recorded in the Semarang City Health Office Data (January to September 2017). Samples were taken in quota with 100 respondents. Data were analyzed by analytic descriptive using chi-square analysis and odds ratio. The results showed behavioral factors to monitor larvae routinely related to the results of larvae examination (p <0,05) with risk factors OR = 5,02 and form observations obtained ABJ in Tembalang District by 89% in 2017. This needs additional attention in the larva monitoring procedure by Semantics and Gasurkes. The more complete the quality of the larvae examination, the existence of larvae can be eradicated, so that the incidence of DHF can be prevented